Effectiveness of nail bed repair in children with or without replacing the fingernail: the NINJA multicentre randomised controlled trial - Jain, A; Greig, A; Taylor, A; Cooper, C; Davies, L; Greshon, A; Fletcher, H; Sierakowski, A; Dritsaki, M; Nguyen, TTA; Png, ME; Stokes, J; et al. (Oxford University Press, 2023)
Background: Surgery for nail bed injuries in children is common. One of the key surgical decisions is whether to replace the nail plate following nail bed repair. The aim of this RCT was to assess the clinical effectiveness and cost-effectiveness of nail bed repair with fingernail replacement/substitution compared with repair without fingernail replacement.